Characterization and analysis of the major risk factors of the Kidney Patients of Bangladesh: a retrospective study - Rahman, Mahmud-Ur (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.